2016
DOI: 10.15294/kemas.v11i2.3694
|View full text |Cite
|
Sign up to set email alerts
|

Dukungan Informasi bagi Ibu-ibu Menyusui dalam Memberikan ASI Eksklusif di Kecamatan Gondokusuman Kota Yogyakarta

Abstract: AbstrakStudi ini bertujuan melihat dukungan informasi seperti apa yang diterima ibu-ibu menyusui dalam memberikan ASI Eksklusif di Kecamatan Gondokusuman Yogyakarta. Penelitian ini adalah penelitian kualitatif dengan pendekatan fenomenologis pada tahun 2015. Data dikumpulkan dengan wawancara mendalam dan focus group discussion. Subjek penelitian ini adalah ibu dengan ASI eksklusif, ibu tidak dengan ASI eksklusif, suami dari ibu menyusui, dan petugas kesehatan. Pemeriksaan keabsahan penelitian menggunakan trian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
10
0
3
Order By: Relevance
“…We found that elderly people with a lot of life experience and a role model still want to show and share the experience of living with loved ones, sharing about everything, ideas and opinions in a variety of life situations that could be accepted in the family. Wibowo (2016), in nursing mothers indicate that the information support is essential for the formation of health behavior in exclusive breastfeeding. According to Simon (1995) in Wibowo (2016), one deteminan health is a social environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that elderly people with a lot of life experience and a role model still want to show and share the experience of living with loved ones, sharing about everything, ideas and opinions in a variety of life situations that could be accepted in the family. Wibowo (2016), in nursing mothers indicate that the information support is essential for the formation of health behavior in exclusive breastfeeding. According to Simon (1995) in Wibowo (2016), one deteminan health is a social environment.…”
Section: Resultsmentioning
confidence: 99%
“…Wibowo (2016), in nursing mothers indicate that the information support is essential for the formation of health behavior in exclusive breastfeeding. According to Simon (1995) in Wibowo (2016), one deteminan health is a social environment. The social environment may include social activities; including interaction between people, friends, neighborhood, and community group activities is a source of information easily in a social environment.…”
Section: Resultsmentioning
confidence: 99%
“…Mothers who are members of mother support community have knowledge and a better attitude about exclusive breastfeeding. Thus, the role of health workers (Arts, 2011), highly influence the decision making of exclusive breastfeeding, as mother will support exclusive breastfeeding when they obtain appropriate information from the health workers (Wibowo, 2016). That is because they consider health professionals know much more about exclusive breastfeeding.…”
Section: Resultsmentioning
confidence: 99%
“…Attention from closest people, such as mothers can not be denied, even pregnant women has been getting supportive information from their parents. In addition, the husband is the mother's partner who has a major contribution to successful toilet training in their children (Wibowo, 2016).…”
Section: Resultsmentioning
confidence: 99%